Arbitrase dan Alternatif Penyelesian Sengketa dalam Penyelesaian Sengketa Ekonomi Syariah - Nurhamidah, Eva; Winario, Mohd; Mairiza, Diany; Dinata, Shidiq Ramdan (EL-EMIR Institute, 2024)
The aim of this article is to resolve conflicts in the field of sharia economics using non-litigation channels. Alternative dispute resolution (APS) is an organization that helps resolve differences of opinion through methods agreed by both parties, such as consultation, negotiation, mediation, conciliation, or expert assessment outside of court. This research uses a library study approach, where books and other library sources are the main material. The choice of this approach is based on the fact that literature studies help researchers in the initial stages of determining and compiling a research framework, as well as deepening theoretical understanding and clarifying the methodology used. Literature studies also function as a way to collect relevant research information. Based on the discussion above, the conclusion is: Alternative Dispute Resolution (ADR) in Islam, such as negotiation, mediation, conciliation and arbitration, has been used since ancient times to resolve conflicts between interested parties. The principles of the Qur'an emphasize the importance of peaceful conflict resolution, both inside and outside the courts. Hadith of the Prophet Muhammad also describe activities comparable to modern ADR, indicating that the ideas of negotiation, mediation, conciliation, and arbitration have long been used in Islamic societies. In practice, Alternative Dispute Resolution (APS) in the early days of Islam showed high flexibility and adaptability, which was in line with the essential ideals taught in Islam, namely justice, peace and social harmony.